Addictive Behavior of Students as Medical and Social Problems of Society, Preconditions for the Formation Addictive Behavior - Sinitskaya, T. (Psychological Prospects Journal, 2013)
The article reviewed the literature on addictive behavior, examined the causes and factors which lead to the development of addiction, analyzed the psychological mechanisms of their formation, and also considered variants of addiction state.